OPERATIONAL RELIABILITY OF RECONSTRUCTED BUILDINGS-STRUCTURES - Saxiba Mirzababaeva (Journals Park Publishing, 2023)
The article talks about the decrease of their initial performance indicators during the use of buildings and structures, and as a result, the quality of structural elements deteriorates. it is analyzed that it gradually decreases, as a result, the service life of the building is reduced, it approaches its limit value, and it gradually reaches its failure limit. It has been proven in the construction practice that the service life of the buildings and structures provided with sufficient maintenance during the operation period is sufficiently increased, and in many cases it serves to prevent dangerous breakdowns and accidental accidents.
Keywords: building, structure, reconstruction, operation, reliability, repairability, durability, boundary, capital repair, urban development, element.